The Global Digital Economy and the Spirit of Indonesian "Product" Nationalism - Mohammad H Holle; Maimuna Toatubun; Arifin Pellu; Magfirah Karanelan (Entrepreneurship and Small Business Research, 2023)
This study aims to determine the position of the Indonesian people's spirit of nationalism in facing today's free and quality global digital economy market. This type of research is literature research with a descriptive qualitative paradigm. This paper used secondary data from Bank Indonesia, UNDP Indonesia, the Indonesian Coordinating Ministry for Economic Affairs, Global Digital Insights, Google and Temasek, Bain & Company, related national and international scientific articles, and various other sources and analyzed inductively. The research results found; First. The development of Indonesia's digital economy is now penetrating many aspects of human life, including culture, technology finance, tourism and the creative economy, in addition to trade, services and other key sectors. All of these sectors have great potential in the global digital economy market. The difficulty of Indonesian MSMEs in developing digital businesses is also influenced by capital and the low power of innovation. Second, the spirit of nationalism for Indonesian products is faced with the development of the global digital economy market, which has the potential to threaten or otherwise grow the country's economy. The degradation of Indonesian nationalism due to the development of the massive global digital economy has greatly affected various aspects of life, including the economy, culture, and lifestyle of the younger generation. Economic nationalism must be used as branding among 270 million Indonesians to love domestic products.